Piano Sonata no. 23, op. 57, published by Simrock (ca. 1837) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Brunsvik, Franz von, 1777-1849 (dedicatee):::Contributor:::::::::::: (N. Simrock; Bonn; Germany)
Piano sonata no. 23 in F Minor, op. 57, later issue of the Simrock edition with lithographed t.p. decorated in blue tint and illustrted with three putti between two pillars